Motivate the crowd or crowd- them out? The impact of local government spending on the voluntary provision of a green public good - Lara Bartels; Martin Kesternich (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Cities are increasingly hold accountable for climate action. By demonstrating their proenvironmentality through own climate-related activities, they not at least aspire to encourage individual climate protection efforts. Based on standard economic theory there is little reason to assume that this is a promising strategy. Financed by taxpayers' money, cities' contributions are considered as substitutes that crowd-out private contributions to the same public good. Inspired by research on providing information on reference group behavior, we challenge this argument and conduct a framed-field experiment to analyze the impact of reference group information on the voluntary provision of a green public good. We investigate whether information on previous contributions by fellow citizens or the city affect individual contributions. We do not find statistical evidence that city-level information crowds-out additional individual contributions. A reference to fellow citizens significantly increases the share of contributors as it attracts subjects that are not per-se pro-environmentally oriented.
Keywords: C93; C83; D9; H41; Q54; 330; Voluntary provision of environmental public goods; Social Norms; Crowding-out; Willingness to pay; Framed-field experiment